Effects of adding enzymes to diets with corn- and sorghum-based dried distillers grains with solubles on growth performance and nutrient digestibility in nursery and finishing pigs - C Feoli; Terry L Gugle; S D Carter; N A Cole; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2008)
Two experiments were conducted to determine the effects of added enzymes on the nutritional value of diets with corn- and sorghum-based dried distillers grains with solubles (DDGS). For Exp. 1, 180 weanling pigs (initially 16.6 lb) were fed the same starter diet for 10 d and then used in a 27-d growth assay. There were 6 pigs per pen and 6 pens per treatment. Treatments were a corn-soybean meal-based control and diets with 30% corn-based (Hudson, SD) and sorghum-based (Russell, KS) DDGS with and without enzymes (a cocktail of β-glucanase, protease, amylase, and xylanase to supply 331, 1,102, 2,205, and 8,818 units of activity, respec-tively, per pound of diet). Pigs fed the control diet had greater (P<0.003) ADG, ADFI, and digestibility of DM, N, and GE than pigs fed the DDGS treatments; sorghum-based DDGS supported worse (P<0.04) F/G and digestibilities of N and GE than corn-based DDGS. Addition of enzymes tended to improve F/G (P<0.09) and did improve digestibility of DM (P<0.04) for pigs fed diets with 30% DDGS, and this response was similar regardless of DDGS source. For Exp. 2, 330 finishing pigs (initially 141 lb) were used in a 65-d growth assay. There were 11 pigs per pen and 6 pens per treatment. Treatments were the same as in Exp. 1, but 40% DDGS was used in diets for the finishing experiment. Pigs fed the control diet had greater ADG, ADFI, and digestibility of DM, N, and GE and lower iodine value than pigs fed the DDGS treatments (P<0.008). Pigs fed the corn-based DDGS treatments had better F/G and digestibility of DM, N, and GE but greater iodine value of jowl fat than pigs fed the sorghum-based DDGS treatments (P<0.04). Enzymes improved digestibility of DM, N, and GE (P<0.01), especially for diets with sorghum-based DDGS (DDGS source × enzyme interaction, P<0.10). In conclusion, growth performance and nutrient digestibility were decreased with addition of DDGS to diets for nursery and finishing pigs, but adding enzymes partially restored the losses in nutrient digestibility.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Digestibility; Dried distillers grains with solubles; enzyme supplementation